Health Literacy and Its Related Factors Among the Elderly in Rasht City, Iran - Afsaneh Nezafati; Nasrin Mokhtari Lake; Farzaneh Sheikholeslami; Ehsan Kazemnezhad Leili (Guilan University of Medical Sciences, 2020)
Introduction: Limited health literacy is a major concern among the elderly because they often need more health information and services to maintain their well-being. Objective: This study was conducted to determine the level of health literacy of elderly members of the National Retirement Fund of Rasht City, Iran. Materials and Methods: The present study was an analytical cross-sectional study conducted on 290 retirees of the National Retirement Fund of Rasht City using the convenience sampling method in 2017. The data collection tool was a questionnaire consisting of two sections: personal profile and functional health literacy of adults (TOFHLA: Test of Functional Health Literacy of Adults). TOFHLA consists of two sections: reading comprehension and numeracy, which includes 67 questions (50 questions related to reading comprehension and 17 questions related to numeracy). The obtained data were analyzed using descriptive and inferential statistics (Chi-square test, Fisher exact-test, analysis of variance, and Independent t-test). Results: The mean±SD age of the participants was 65.38±4.96 years. About 52.1% of the subjects were men and the rest were women. Also, 54.8% had adequate health literacy. The highest mean±SD score of health literacy was in the field of reading comprehension (36.30±7.90) and the field of numeracy (36.11±11.60). A statistically significant relationship was observed between the level of health literacy and the level of education (P=0.001) and between the level of education of the spouse (P=0.0001) and the history of cancer (P=0.008). Conclusion: This study showed that about half of the elderly studied had poor health literacy. Providing appropriate training programs may be effective in improving the health of the elderly.